Factors influencing integration of web-based instruction by secondary school English language teachers - Sayadian, Sima (2012)
The current study investigated the factors that influence the adoption and integration of Web-Based Instruction (WBI) by secondary school teachers in Malaysia. Also, this investigated the relationship between the five attributes of the Diffusion of Innovations Model, National Educational Technology Standards for Teachers (NETS•T), teachers’ demographic variables and WBI adoption and integration by TESL (Malaysian) secondary school teachers as well as their stages of concern with regard to WBI application. Data were collected from 450 secondary school English language teachers in Malacca, Malaysia. A questionnaire comprising of five separate sections (demographic variables, attributes of diffusion of innovation based on Roger’s model, National Educational Technology Standards for Teachers, different types of technology adopters, stages of concern) was selected as the instrument of the quantative phase of the study and a semi structured interview was chosen as the instrument for the qualitative phase of the research to help find out about the tentative barriers which may have caused hinderance in technology application from teachers and to identify how their stages of concern are related to their perceived characteristics of technology application and integration. Analysis of data showed that the attributes of diffusion of innovation correlated with WBI integration (r=0.525). Also, descriptive statistics indicated the most frequent attribute of diffusion of innovation was “Relative Advantage” (Mean=3.59) while the least frequent attribute was shown to be “Trialibility” (Mean= 3.11). Similarly, t-test showed no significant relationship between demographic variables and WBI application except for gender (t=2.319, sig=0.22). A positive correlation was reported between NETS*T and WBI integration (r=0.516). Finally, it was shown that the barriers for WBI application among Malaysian secondary school teachers included Time, teacher's role, students’ readiness, distraction, language proficiency Access to computer facilities. English language secondary school teachers in Malacca have the highest degree of concern in stage 0 which is awareness; so, they fall in “Non-users” category. In conclusion, this study suggests the need for more professional development programs and training sessions for the English language teachers to be well-informed on their awareness in technology integration in their classes.